Blending Foreign Policy with Nepal’s Geostrategic Location - Khanal, Gopal (Journal of Foreign Affairs, 2022)
Over the course of a century, the Western world’s power hegemony has gradually shifted to Asia. China is emerging as a superpower with technological advancement, cashless transactions, 5Gdevelopment, and one of the most powerful military forces. China’s power in Asia has added worries to the United States of America. The purpose of this research is to emphasize Nepal’s geostrategic location and its impact on foreign policy. Nepal is located between the two rising economies in the world, China, and India, who have had conflicting and competitive relations, and therefore requires to delicately balance its relations given the sensitive geopolitical location. But it doesn’t mean Nepal should compromise her sovereignty and territorial integrity while maintaining geopolitical balance. Similarly, India and China need to respect the sovereignty and territorial integrity of Nepal. This has been a major challenge for Nepal to design its foreign policy based on sound geopolitical theories. Although literature on Nepal’s geostrategic importance is limited, this paper explores the impact of its geographic location on foreign policy in the changing global order.